Beliefs in the Komburongo (Acorus Calamus) and its spiritual healing among the Dusunic people of Sabah, Malaysia - Low, Kok On; Soleha Ishak (American Scientific Publishers, 2016)
In Sabah, Malaysia, the Komburongo or the sweet flag plant plays an important role in the lives and rituals of the Dusunic ethnic people, who believed that this plant is actually a form of spiritual helper, able to obstruct evil spirits and prevent them from doing harm during spiritual healings. The aim of this field research, based on interviews and direct observations, is to record and document the information given orally by the believers and practitioners of ritual healings. This research focuses on the importance of the Komburongo, in its many guises as spiritual helper, sacred ritual instrument and obstructer of evil in combating the invisible powers in spiritual healings as practised by selected Dusunic ethnic groups in Sabah. Currently, after they became either Christians or Muslims, belief in the Komburongo and spiritual healings have become less dominant.